2020
DOI: 10.1128/jvi.01553-19
|View full text |Cite
|
Sign up to set email alerts
|

USP7-Dependent Regulation of TRAF Activation and Signaling by a Viral Interferon Regulatory Factor Homologue

Abstract: Human herpesvirus 8 (HHV-8) encodes four viral interferon regulatory factors (vIRFs 1 to 4), all of which are expressed during lytic replication and inhibit a variety of antiviral signaling pathways. Viral IRFs 1, 2, and 3 are also expressed during latency in primary effusion lymphoma (PEL) cells, and vIRF-1 and vIRF-3 have been reported to promote PEL cell viability. Viral IRFs 1, 3, and 4 are known to interact with ubiquitin-specific protease 7 (USP7); interactions of vIRF-1 and vIRF-3 with USP7 promote PEL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…In our study, P22077 did not appear to impact the K63linked ubiquitination of TRAF6. But Xiang et al reported that USP7 regulated the K63-linked polyubiquitination of TRAF3 and TRAF6 [42], indicated that USP7 regulating polyubiquitination of TRAF6 maybe difference in different stimulus. Furthermore, our data suggest that small molecule inhibitor of DUBs maybe an excellent antiinflammatory drug with potential clinical application.…”
Section: Agingmentioning
confidence: 99%
“…In our study, P22077 did not appear to impact the K63linked ubiquitination of TRAF6. But Xiang et al reported that USP7 regulated the K63-linked polyubiquitination of TRAF3 and TRAF6 [42], indicated that USP7 regulating polyubiquitination of TRAF6 maybe difference in different stimulus. Furthermore, our data suggest that small molecule inhibitor of DUBs maybe an excellent antiinflammatory drug with potential clinical application.…”
Section: Agingmentioning
confidence: 99%
“…NLRP3 [38] Regulates NLRP3 inflammasome activation [38] NF-κB [39], NEMO [33] Regulates NF-κB signaling [33,39] VP24 [49] Involves in virus replication [49] Tat [50] Involves in virus production [50] TRAF3/TRAF6 [51] Modulates antiviral signaling [51] TRAF6/IKKγ [34] Regulates TLR signaling [34] USP-10 CFTR [37,52] Epithelial mucosal clearance [37,52] NICD1 [53] Regulates Notch signaling [53] USP-11 E2F1 [54] Regulates lung epithelia proliferation and wound healing [54] LPA1 [36] Enhances inflammation [36] USP-13 IL-1R8/Sigirr [40] Suppresses lung inflammation [40] PTEN [41] Regulates cell apoptosis [41] MCL1 [42] Regulates transformation of fibroblasts [42] STAT1 [55] Regulates IFN Signaling [55] STING [56] Negatively regulates antiviral responses [56] USP-14 I-kB [31] Increases cytokine release [31] CBP [32] Lung inflammation [32] USP-15 IκBα [57] NF-κB activation [57] USP-17 HDAC2 [58] Reverses glucocorticoid resistance [58] TRAF2/TRAF3 [59] Lung inflammation [59] [92] Inhibits type I IFN signaling and antiviral response [92] POH1 pro-IL-1β [93] Negatively regulates the immune response [93] BRCC3 NLRP3…”
Section: Dubsmentioning
confidence: 99%
“…USP7 (HAUSP)is originally identified as a viral binding protein that preferentially cleaves K11-, K63-and K48-linked ubiquitin chains [119,120]. USP7 is involved in viral infection by targeting virus related protein to modulate virus replication and production [49][50][51]. USP7 is reported to deubiquitinate and stabilize NF-κB to increase its transcriptional activity in TLR-induced inflammatory gene expression [39].…”
Section: Uspsmentioning
confidence: 99%
“…Nonetheless, the actual functions of the vIRFs and particular vIRF-protein interactions in HHV-8 de novo infection, latency, and productive replication are still poorly understood. However, it is known that in PEL cells, vIRFs 1, 2 and 3, which are expressed at least to some degree in the latent phase, support PEL cell viability, and in lytic replication, vIRF-1 has been shown to promote virus production from PEL cells and iSLK epithelial cells (inducible for immediate-early RTA expression and used experimentally to host genetically modified HHV-8) and viral lytic gene expression in the former [8][9][10][11]. Counterintuitively, vIRF-2 and vIRF-3 inhibit productive replication in PEL and iSLK cells, as does vIRF-2 in HuARLT endothelial cells [9,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that in PEL cells, vIRFs 1, 2 and 3, which are expressed at least to some degree in the latent phase, support PEL cell viability, and in lytic replication, vIRF-1 has been shown to promote virus production from PEL cells and iSLK epithelial cells (inducible for immediate-early RTA expression and used experimentally to host genetically modified HHV-8) and viral lytic gene expression in the former [8][9][10][11]. Counterintuitively, vIRF-2 and vIRF-3 inhibit productive replication in PEL and iSLK cells, as does vIRF-2 in HuARLT endothelial cells [9,10,12]. Indeed, identified activities of vIRF-2 include the activation of innate immune signaling leading to interferon induction, direct induction of interferon-stimulated genes, and specific repression of early viral genes [10,12].…”
Section: Introductionmentioning
confidence: 99%